Dissociation of Platelet Activation and Spontaneous Myocardial Ischemia in Unstable Angina - Vejar, Margarita; Fragasso, Gabriele; Hackett, David; Lipkin, David P; Maseri, Attilio; Born, Gustav V R; Ciabattoni, Giovanni; Patrono, Carlo (Thrombosis and Haemostasis, 1990)
A dynamic thrombotic process, coronary spasm or both can be responsible for recurrent episodes of transient reduction of coronary blood flow in unstable angina. We have investigated the temporal relationship between episodic platelet activation, as detected by increased urinary excretion of 11-dehydro-TXB2, and spontaneous myocardial ischemia, assessed by continuous electrocardiographic monitoring and recording in 21 patients with unstable angina pectoris. In order to validate measurements of metabolite excretion as a reflection of intracoronary platelet activation, we have also performed repeated urine sampling from 8 patients undergoing PTCA and from 6 patients with peripheral vascular disease. The latter showed a 16% coefficient of variation in 3 consecutive 8-h urine samples. 11-dehydro-TXB2 increased significantly, by up to 15-fold, in the 2.5- to 5.0-h urine collection encompassing PTCA and decreased by > 50% during the following 2-h period. Patients with unstable angina were characterized by episodic increases (>2 SD of controls) in metabolite excretion, in successive 6-8 h specimens. Paired measurements of 11-dehydro-TXB2 and 2, 3-dinor-TXB2 in 15 urine samples did not reveal evidence of altered metabolic disposition of endogenously released TXB2. A total of 125 ECG ischemic episodes were recorded, of which 64% asymptomatic. We have compared these biochemical and ECG changes in patients randomized to i. v. low-dose aspirin or i.v. isosorbide dinitrate and oral diltiazem. Twenty-five of 56 (i.e. 45%) urine samples obtained in aspirin-free periods showed increased metabolite excretion as compared to 15 of 88 (i.e. 17%) samples collected during aspirin. Of the former, only 3 episodes of enhanced 11-dehydro-TXB2 excretion were associated with ST-segment changes, 7 with chest pain, and 15 with no ECG or clinical changes. Metabolite excretion was approximately 70% lower during aspirin administration than during coronary dilators. However, despite > 95% suppression of platelet cyclooxygenase activity, as monitored ex vivo, incomplete suppression of in vivo TXB2 biosynthesis was occasionally seen during low-dose aspirin therapy. We conclude that in unstable angina, episodic platelet activation is infrequently associated with spontaneous myocardial ischemia. Although the two events may represent functional expressions of the same coronary lesion, they are likely to be triggered by independent mechanisms through different mediators.